2016
DOI: 10.1097/qad.0000000000000874
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clearance of anal high-risk human papillomavirus in HIV-positive men who have sex with men

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 30 publications
8
41
1
1
Order By: Relevance
“…Third, the collected data on the potential risk factors were not comprehensive. For example, the information on the number of sex partners and on the diagnosis time for those reported a history of genital warts was not collected in the present study, which limited to provide more evidences for risk factor analysis [24].…”
Section: Discussionmentioning
confidence: 97%
“…Third, the collected data on the potential risk factors were not comprehensive. For example, the information on the number of sex partners and on the diagnosis time for those reported a history of genital warts was not collected in the present study, which limited to provide more evidences for risk factor analysis [24].…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, HPV infection, which may facilitate the invasion of pathogens, is a significant risk factor (3.5-times increased risk) for HIV acquisition [6]. Similarly, HIV infection can increase the risk of HPV infection and the failure of HPV clearance through weakening the immune function of the body [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study, that analysed the incidence and clearance of anal high-risk human papillomavirus in HIV-positive MSM, found that those with low HIV-RNA-viral load had the highest clearance [43]. Classically, youth has been associated with the infection of HPV in anal mucosa [8].…”
Section: Discussionmentioning
confidence: 99%